Analisis Unsur-Unsur Pendidikan Masa Lalu Sebagai Dasar Penentuan Arah Kebijakan Pembelajaran Pada Era Globalisasi - Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2018)
This article aims to analyze the elements of education that have been applied and problems encountered in the past, as well as determining the basis of educational policies that are applied in the globalization era. Elements of education in the past continuously strived for improvement and improvement to a better direction. Basic education policies that can be applied in the future include (1) the transformation of school education to the XX1 century, (2) need to understand the significance of modernization and modernity, (3) modern life filled with inequalities, contradictions and progress can make human lose its meaning in life, to avoid this it is recommended a general education program that gives students the ability to capture the various types of meaning contained in education, and (4) learners need more emphasis on historical education, history is a lesson given to the students to understand why a society in a given time in the past took a certain decision in the face of a particular problem. Students are gradually guided to grasp the meaning of what is behind the visible or physically felt, the students are trained to understand the meaning of the small meaning to the great meaning of the meaning of life itself.